The Conflict Between Individuals and Global Corporations – The Communication Context - Zalewska-Turzyńska, Magdalena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The communication is, no doubt, the main tool in managing corporation. In this context, there is corporation – the employee should be in contact (via e-mail, mobile phone), and employee – human need for balance (work, rest, sleep). This leads to the conflict, both parties looses – companies: competence in personnel, employees: pronouncing the contract. This is, obviously, simplified point of view. Since it is inconvenient it should be changed. Is it possible to change continuous communication stand-by? Will it influence reaching the higher level of organizational development? Here is the opinion to share.